Validation of droplet digital PCR for the detection and absolute quantification of Borrelia DNA in Ixodes scapularis ticks - KING, JENNY L.; SMITH, ASHLEY D.; MITCHELL, ELIZABETH A.; ALLEN, MICHAEL S. (Parasitology, 2017)
We evaluated the QX200 Droplet Digital PCR (ddPCR™, Bio-Rad) system and protocols for the detection of the tick-borne pathogens Borrelia burgdorferi and Borrelia miyamotoi in Ixodes scapularis nymphs and adults collected from North Truro, Massachusetts. Preliminary screening by nested PCR determined positive infection levels of 60% for B. burgdorferi in these ticks. To investigate the utility of ddPCR as a screening tool and to calculate the absolute number of bacterial genome copies in an infected tick, we adapted previously reported TaqMan®-based qPCR assays for ddPCR. ddPCR proved to be a reliable means for detection and absolute quantification of control bacterial DNA with precision as low as ten spirochetes in an individual sample. Application of this method revealed the average carriage level of B. burgdorferi in infected I. scapularis nymphs to be 2291 spirochetes per nymph (range: 230–5268 spirochetes) and 51 179 spirochetes on average in infected adults (range: 5647–115 797). No ticks naturally infected with B. miyamotoi were detected. The ddPCR protocols were at least as sensitive to conventional qPCR assays but required fewer overall reactions and are potentially less subject to inhibition. Moreover, the approach can provide insight on carriage levels of parasites within vectors.